PERAN UNESCO DALAM KEBIJAKAN KOTA INKLUSIF BAGI PENYANDANG DISABILITAS DI KOTA BANJARMASIN DALAM RANGKA MENDUKUNG TUJUAN PEMBANGUNAN BERKELANJUTAN KE-11 TAHUN 2017-2019 - Dike Aseilla (2022)
This study aims to discuss the role of UNESCO in inclusive city policies for persons with disabilities in Banjarmasin City by using the concept of the function and role of international organizations and the concept of sustainable development goals that focus on the 11th goal, namely safe, inclusive, and sustainable cities and communities. The method used is qualitative-descriptive by using interview data sources and supporting documents. The final result of this study shows that UNESCO plays a role in inclusive city policies in the City of Banjarmasin which is shown in several activities such as the establishment of the Indonesian Mayor Network Charter Towards Inclusive Cities, Inclusive City Assessment Instruments, implementing participatory data collection projects for persons with disabilities, holding a Mayor's High Level Meeting for the 8th Inclusive City and conducted a Data-Based Disability Inclusive City Planning and Development Workshop in Banjarmasin. The contribution provided is a policy input for the Banjarmasin City Government such as determining the concentration area for disabilities, improving public transportation, fulfilling political rights, and launching social services for people with disabilities in Banjarmasin City.